On effect of primed cellular microcapsules and pH neutralizing biomaterials to augment regeneration of the intervertebral disc - GANSAU, JENNIFER (Trinity College Dublin. School of Engineering. Discipline of Mechanical & Manuf. Eng, 2020)
One of the most common topics of research worldwide for medical health care is low back pain (LBP). It is widely accepted that LBP is associated with degeneration of the intervertebral disc (IVD), the shock absorbent soft tissue between the vertebral bodies. Degenerative discs disease (DDD) is characterised by increased cell death and loss in structural extracellular matrix (ECM) molecules within the nucleus pulposus (NP) tissue, the highly hydrated gelatinous tissue in the centre of the IVD. Being an avascular structure, the nutrient supply within the IVD is limited, resulting in a compromised microenvironment with limited oxygen and glucose, and a low pH. These can drop even lower during the progression of disc degeneration resulting in further cell death and loss of structural integrity. Cell-based therapy has been proposed to re-establish the natural cell population within the disc and subsequentially re-produce matrix molecules for a healthy IVD. Some success has been made using NP cells, yet shortcomings for a long-term solution remain such as poor cell yield post-isolation, limited matrix forming capacities, and cell death and leakage during re-injections. The overall objective of this thesis was to develop an injectable biomaterial that successfully delivers cells into the disc while preserving their capability to sustain the harsh microenvironment characteristic of degenerative disc. Specifically, this thesis investigates i) technical challenges associated with intradiscal injections of cells (i.e. cell damage due to shear forces) by establishing a material for consistent delivery into the disc and ii) a strategy to overcome the microenvironmental limitations found in degenerated disc, with specific focus on the acidic pH. The thesis began by characterizing the electrohydrodynamic spraying (EHDS) technology for microencapsulation of cells into ionically crosslinked alginate hydrogels. Adjusting the operation settings, injectable microcapsules (μCaps) were successfully fabricated with entrapped cells in an optimised seeding density for matrix accumulation. These were further capable to sustain shear stress during injection through a needle. Thereafter, a viscous bulking agent was developed using a fibrin-hydrogel base to enhance μCap delivery into the highly pressurized IVD. A fibrin-hyaluronic acid (HA) blend was found to induce increased proliferation and matrix deposition of cells, making the advantages of the bulking agent two-fold: i) enhanced μCap delivery into the disc and ii) promoted disc-like tissue formation for better regeneration potential. The thesis continued by exploring a way to improve cellular response to the acidic environment of the IVD. Three different pH conditions (pH 7.1, 6.8 and 6.5), representative for different stages of disc degeneration, were investigated using articular chondrocytes (AC) and bone marrow-derived stem cells (BMSC) with and without priming using TGF-β3. By priming the cells, the detrimental pH effect observed on cells without priming was overcome with significantly improved viability and ECM levels for both cell types in all pH levels investigated. Finally, the challenging acidic microenvironment was altered using pH neutralizing antacids. After applying EHDS to fabricate antacid microcapsules, efficient pH increase was found using CaCO3 nanoparticles inside alginate μCaps with a slow release kinetics for long lasting neutralization effects. Exploring the established hybrid-hydrogel containing EHDS fabricated cellular μCaps (AC or BMSC) and CaCO3 μCaps within the fibrin-HA bulking gel, within a disc explant model, elevation of core pH was successfully established. Moreover, improved matrix retention within the disc tissue was accomplished with both cell types, AC and BMSC. To conclude, this thesis describes a novel approach to develop an injectable material for minimally invasive treatment of the degenerated IVD. A hybrid hydrogel was established containing i) μCaps with primed cells to deposit de novo matrix into the acidic microenvironment of the disc and aid resident cells to re-establish their potential by paracrine signalling, ii) μCaps containing CaCO3 nanoparticles to elevate local pH and subsequentially enhance cell viability and matrix accumulation of resident cells and iii) a fibrin-HA bulking agent to facilitate μCap deposition into the IVD while promoting cell proliferation and disc-like matrix accumulation.
APPROVED
Keywords: Intervertebral Disc; Low Back Pain; Biomaterials; cell-based therapy